Host genetic factors and vaccine-induced immunity to HBV infection: haplotype analysis - Ryckman, K; Fielding, K; Hill, A; Mendy, M; Rayco-Solon, P; Sirugo, G; Van Der Sande, MA; Waight, P; Whittle, H; Hall, A; Williams, S; Hennig, B (Public Library of Science, 2010)
Hepatitis B virus (HBV) infection remains a significant health burden world-wide, although vaccines help decrease this problem. We previously identified associations of single nucleotide polymorphisms in several candidate genes with vaccine-induced peak antibody level (anti-HBs), which is predictive of long-term vaccine efficacy and protection against infection and persistent carriage; here we report on a haplotype-based analysis. A total of 688 SNPs from 117 genes were examined for a two, three and four sliding window haplotype analysis in a Gambian cohort. Analysis was performed on 197 unrelated individuals, 454 individuals from 174 families, and the combined sample (N = 651). Global and individual haplotype association tests were carried out (adjusted for covariates), employing peak anti-HBs level as outcome. Five genes (CD44, CD58, CDC42, IL19 and IL1R1) had at least one significant haplotype in the unrelated or family analysis as well as the combined analysis. Previous single locus results were confirmed for CD44 (combined global p = 9.1×10−5 for rs353644-rs353630-rs7937602) and CD58 (combined global p = 0.008 for rs1414275-rs11588376-rs1016140). Haplotypes in CDC42, IL19 and IL1R1 also associated with peak anti-HBs level. We have identified strong haplotype effects on HBV vaccine-induced antibody level in five genes, three of which, CDC42, IL19 and IL1R1, did not show evidence of association in a single SNP analyses and corroborated the majority of these effects in two datasets. The haplotype analysis identified associations with HBV vaccine-induced immunity in several new genes.